A nonisothermal phase‐field model for the ferromagnetic transition. (14th September 2012) - Berti, V.; Grandi, D.
<x xml:space="preserve">Abstract</x> We propose a model for nonisothermal ferromagnetic phase transition based on a phase field approach, in which the phase parameter is related but not identified with the magnetization. The magnetization is split in a paramagnetic and in a ferromagnetic contribution, dependent on a scalar phase parameter and identically null above the Curie temperature. The dynamics of the magnetization below the Curie temperature is governed by the order parameter evolution equation and by a Landau–Lifshitz type equation for the magnetization vector. In the simple situation of a uniaxial magnet, it is shown how the order parameter dynamics reproduces the hysteresis effect of the magnetization. Copyright © 2012 John Wiley & Sons, Ltd.